PENERAPAN SANKSI KEBIRI KIMIA TERHADAP PELAKU TINDAK PIDANA SEKSUAL TERHADAP ANAK - Dahwir, Ali; Barhamudin, Barhamudin (Faculty of Law, University of Palembang, 2021)
Sexual crimes that make children as victims are extraordinary crimes that threaten and endanger children's psychology and can eliminate comfort, peace, security, and order in society. The problem discussed in this paper is how to apply chemical castration sanctions to perpetrators of sexual crimes against children. In answering the existing problems, using normative legal research methods are descriptive analytical. The analysis was carried out qualitatively, using a legal approach, a case approach and a philosophical approach. The results showed that the Indonesian Doctors Association did not want to be the executor of chemical castration punishment, this was because doctors were bound by an oath and a code of medical ethics. In this code of ethics, philosophically, doctors have the task of trying to heal, not vice versa, namely by using science to carry out actions that are contrary to humanity, namely revoking a person's health even if only temporarily. It is the duty of the police to enforce the law against the decisions made by the court. The execution can be carried out by nurses and skilled personnel free from the oath of office. Nurses carry out castration injections on the basis that they have met the criteria that have been set as requirements for providing health services, as regulated in the Nursing Act.